Increasing incidence of type 1 diabetes among Korean children and adolescents: analysis of data from a nationwide registry in Korea. Issue 7 (30th September 2015) - Kim, Jae Hyun; Lee, Chong Guk; Lee, Young Ah; Yang, Sei Won; Shin, Choong Ho
Abstract : Background: The incidence of type 1 diabetes mellitus (T1DM) in children and adolescents has increased worldwide. However, the epidemiology of T1DM among Korean youth has not been reported since 2001. We investigated the incidence of T1DM in Korean children and adolescents from 2012 to 2014 and compared it with data from 1995 to 2000. Patients and Methods: Data were obtained from the National Health Insurance Service (NHIS) registry, and age‐ and sex‐specific incidence rates were calculated per 100 000 population. Results: In total, 706 patients (326 boys and 380 girls, aged <15 yr) with T1DM were registered in the NHIS during 2012–2014. The incidence rate per 100 000 population was 3.19 (95% confidence interval [CI] 2.96–3.43). We found incidence rates of 1.68, 3.16, and 4.46 in children 0–4, 5–9, and 10–14 yr, respectively. The T1DM incidence was 2.84 in boys and 3.56 in girls. A higher T1DM incidence was seen during 2012–2014 than from 1995–2000 (incidence rate ratio 2.33; p < 0.001). The incidence rate ratios between 1995–2000 and 2012–2014 were 2.31, 2.20, and 2.27 in children 0–4, 5–9, and 10–14 yr, respectively. The annual increase in T1DM incidence was 5.6% (95% CI 5.0–6.3%) between 1995 and 2014. Conclusions: We observed a significant increase in the T1DM incidence. This increase was higher in boys than in girls, and was highest in children aged 0–4 yr. Studies are needed to evaluate the long‐term epidemiological trend of T1DM incidence.